New insights of propolis nanoformulation and its therapeutic potential in human diseases - Kustiawan, Paula Mariana; Syaifie, Putri Hawa; Siregar, Khalish Arsy Al Khairy; Ibadillah, Delfritama; Mardliyati, Etik (ADMET & DMPK, 2024)
Background and purpose: Scientific research is crucial to develop therapies for various disease severity levels, as modern drugs cause side effects and are difficult to predict. Researchers are exploring herbal alternatives with fewer side effects, particularly propolis, which has been validated through in vitro, in vivo, and clinical studies. This will focus on scientific evidence and its supporting technology for developing new bioactive compounds for chronic diseases. Nanotechnology can improve the delivery and absorption of herbal medicines, which often have poor bioavailability due to their high molecular weight and solubility in water, particularly in oral medicines. This technology can enhance propolis's effects through multi-target therapy and reduce side effects. Experimental approach: All publications related to each section of this review were discovered using the search engines Google Scholar, Scopus, and Pubmed. This was only available for publication between 2013 and 2023. The selected publications were used as references in this review after being thoroughly studied. Key results: Evaluation of propolis active compounds, the classification of propolis nano formulations, design concepts, and mechanisms of action of propolis nano formulation. Additionally, the challenges and prospects for how these insights can be translated into clinical benefits are discussed. Conclusion: In the last ten years, a list of nanoformulation propolis has been reported. This review concludes the difficulties encountered in developing large-scale nanoformulations. To commercialize them, improvements in nano carrier synthesis, standardized evaluation methodology within the framework of strategy process improvement, and Good Manufacturing Practices would be required.